Literature Review: Review of Curriculum Educational Administration - Sani Septiana; Asep Mulyana; Tanti Fitri Yana (Konsultan Jurnal Ilmiah Indonesia, 2025)
This article was written to know Definition of Curriculum Educational Administration Review. The method used to write this article is the library research method, which collects data from various sources of literature. The article explains that the syllabus is a set of plans and provisions for content, materials and learning methods that guide the implementation of the learning process. The curriculum management process includes curriculum administration. such as planning, developing, implementing, evaluating, and improving the curriculum. Curriculum development requires a solid foundation and is based on careful thought and research. And the assessment or assessment in the syllabus helps to assess syllabus achievements. From this we can see that the role of the curriculum in formal education in schools is very important and has a very big influence on the achievement of educational goals. Teachers act as technical actors: actors, adapters, developers, and researchers.